Cu-based quaternary chalcogenide Cu2BaSnS4 thin films acting as hole transport layers in inverted perovskite CH3NH3PbI3 solar cells. Issue 6 (23rd January 2017) - Ge, Jie; Grice, Corey R.; Yan, Yanfa
Abstract : p-Type wide-bandgap Cu2 BaSnS4 holds promise for use as hole transport material in inverted perovskite CH3 NH3 PbI3 thin-film solar cells. Abstract : Efforts toward developing efficient and stable inorganic hole transport materials for inverted perovskite CH3 NH3 PbI3 solar cells are underway. Herein, a wide bandgap p-type quaternary chalcogenide Cu2 BaSnS4 semiconductor is demonstrated as a promising hole transport material in inverted perovskite CH3 NH3 PbI3 thin-film solar cells owing to its satisfactory chemical stability, high carrier mobility (∼10 cm 2 V −1 s −1 ), and suitable band alignment with CH3 NH3 PbI3 . Our inverted solar cell based on a 100 nm thick Cu2 BaSnS4 hole transport layer achieves a best PCE of ∼10% with a low degree of current–voltage scan hysteresis.